2013
DOI: 10.1084/jem.20131195
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy activates cancer-associated fibroblasts to maintain colorectal cancer-initiating cells by IL-17A

Abstract: Chemotherapy stimulates cancer-associated fibroblasts to secrete interleukin-17A to provide maintenance cues to support the growth of colorectal cancer-initiating cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
266
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(275 citation statements)
references
References 98 publications
(155 reference statements)
9
266
0
Order By: Relevance
“…Previous studies have demonstrated that stromal compartments are changed by cytotoxic therapies (14,15), indicating microenvironment-associated drug resistance. Therefore, the stromal response in the MTD and LDM groups treated with 5-Fu or capecitabine was examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that stromal compartments are changed by cytotoxic therapies (14,15), indicating microenvironment-associated drug resistance. Therefore, the stromal response in the MTD and LDM groups treated with 5-Fu or capecitabine was examined.…”
Section: Resultsmentioning
confidence: 99%
“…The significant increase in the amount of CAFs following chemotherapy indicated that chemotherapy may induce the remodeling of the tumor microenvironment as well, and CAFs may offer microenvironmental cues instructing tumor drug resistance (14,21). In vitro assays have also demonstrated that CAFs induce resistance to chemotherapy via secreting cytokines (16,22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, depleting stroma-derived WNT16B, which would specifically overcome such a "new" but not "minor" TME-associated resistance mechanism [57,60]. As supporting evidence, CAFs are similarly enriched in colorectal cancer (CRC) during the post-therapy stage and display enhanced cytokine IL-17A, which helps maintain the tumor infiltrating cells (TICs) through activation of NF-κB signaling [61].…”
Section: The Therapeutically Remodeled Tme Alters Clinical Outcomementioning
confidence: 98%
“…It is quite established that cancer cells obeying to the operational definition of "stem cells" are highly resistant to conventional therapies, and thus are the most likely cause of tumor recurrence (30). In colorectal C-IC, chemoresistance has been associated with the activity of autocrine IL4 (37), or the paracrine stimulation by IL17A, a factor that promotes also self-renewal (38), or the activity of transcription factors ID1 and ID3, critical for sustaining the stem phenotype (32). Altogether, these data support the conclusion that "determinants of stemness" deeply contribute to therapeutic resistance (30) and enhance the interest in the stemness promoting activity of HGF as a cause of failure of conventional and targeted therapy.…”
Section: Colorectal Cancer Stem Cells: the Root Of The Tumor Resistanmentioning
confidence: 99%